New Trends in 3D Printing 2016
DOI: 10.5772/63411
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing Cardiovascular Anatomy: A Single-Centre Experience

Abstract: This chapter presents the experience of the cardiac engineering team within the Centre for Cardiovascular Imaging at Great Ormond Street Hospital for Children (London, UK) in using three-dimensional (3D) printing technology. 3D models can serve different functions towards implementing a patient-specific approach for studying and potentially treating congenital heart disease (CHD). In order to showcase different potential applications, this chapter discusses not only clinical case studies and engineering experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…(10, 41) A broad range of complex congenital heart anatomies have been reconstructed and 3D printed to enhance surgical planning including: double-outlet right ventricle; (26, 42) atrial septal defect (ASD) and ventricular septal defect (VSD);(18, 38, 43, 44) Tetralogy of Fallot(35, 45) as well as hypolastic left heart syndrome. (12, 27, 36) Moreover it has been shown that 3D printed models may assist with the accuracy of ventricular assist device (VAD) cannula placement in patients with congenital heart disease. (42) Detailed reviews of cardiac congenital 3D printed modeling have recently been published.…”
Section: Cardiovascular Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…(10, 41) A broad range of complex congenital heart anatomies have been reconstructed and 3D printed to enhance surgical planning including: double-outlet right ventricle; (26, 42) atrial septal defect (ASD) and ventricular septal defect (VSD);(18, 38, 43, 44) Tetralogy of Fallot(35, 45) as well as hypolastic left heart syndrome. (12, 27, 36) Moreover it has been shown that 3D printed models may assist with the accuracy of ventricular assist device (VAD) cannula placement in patients with congenital heart disease. (42) Detailed reviews of cardiac congenital 3D printed modeling have recently been published.…”
Section: Cardiovascular Applicationsmentioning
confidence: 99%
“…In another example, a previously stented aortic coarctation with an abnormal subclavian artery originating from the stent site was 3D printed prior to a repeat intervention. (figure 4) (36). …”
Section: Cardiovascular Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Arterial Phantoms 3D-printed blood vessels are increasingly being used to visualize patient-and pathology-specific states in the field of cardiovascular surgery. Preoperatively, 3D-printed blood vessels can facilitate the selection and intended location of endovascular stents in complex aortic aneurysms and coarctations (16)(17)(18). Likewise, in other settings, 3D-printed blood vessels have been employed to aid surgical practice amongst medical trainees and to evaluate the utility of imaging technologies in endovascular interventions (19,20).…”
Section: Future Developmentsmentioning
confidence: 99%